Analysis of Students’ Difficulties in Story Problems Division Reviewed from Mathematical Representation and Polya’s Stages In Elementary School - Ika Rahmawati; Rosadelita Prima Siwi; Neni Mariana (JENIUS (Journal of Education Policy and Elementary Education Issues), 2026)
The ability to solve story problems division is highly dependent on students' mathematical representation and structured problem-solving skills, yet many students still experience difficulties in this area. This study aims to describe the difficulties of 5th-grade students in solving division story problems in terms of mathematical representation and Polya's stages. This study used a descriptive qualitative research design. The participants consisted of 18 fifth-grade students of SD Negeri 4 Gamping, all of whom were involved in the primary analysis through a written test. Based on their combined scores in mathematical representation and Polya's stages, students were classified into high, middle, and low categories. Using purposive sampling, three students representing each category were selected as subjects for subsequent in-depth qualitative interviews The results show: (1) high-category students have no difficulty in using symbolic, visual, or verbal representation; middle-category students are able to use symbolic and visual representation but are more proficient verbally in oral form than in writing; and low-category students experience difficulty in using all three forms of representation; (2) in terms of Polya's stages, students have a tendency to skip the first stage of understanding the problem and proceed directly to planning and implementing solutions; (3) students' mathematical representation ability significantly influences their thinking process in solving story problems. This study concludes that students' difficulties in solving story problems division are rooted in their low mathematical representation abilities, which in turn impede Polya's problem-solving stages. Practically, these findings help teachers see exactly why students get confused by functional texts, allowing them to provide the right help in class.